Gamification Analysis for Motivation and Engagement Using Running Apps - Nia Karlna; Arsa Widitiarsa Utoyo; Emmanuel Himawan Saptaputra (Journal of Games, Game Art, and Gamification, 2019)
Gamification is the application of game features, mainly elements of video games, in a context not related to the game in order to promote motivation and commitment to learning. The application of gamification in a pedagogical context provides some remedy for many people who feel alienated from traditional teaching methods. The use of gamification could provide a partial solution to the decrease in the motivation and commitment of the students that the user faces today. Specifically, the younger environment could benefit greatly from gamification not only for its enjoyment but also for a healthy life. This critical analysis of gamification literature wants to be part of a sequence on the effect of gamification on motivation and commitment. A methodology proposed in the study of the effects of gamification in motivation and commitment, as well as an empirical study, consists of a smartphone application that provides tracking and gamification elements. While the control arm consists of on an application designed identically only with the characteristics of tracking health information. The proposal will be made among young people who use applications on the day off from cars in Jakarta